Functional Characterization of Dark Sleeper (Odontobutis obscura) TBK1 on IFN Regulation - Chen, Jian; Li, Zhuo Cong; Lu, Long Feng; Li, Pei; Li, Xi-Yin; Li, Shun (Frontiers in Immunology, 2019)
In East Asia, the dark sleeper, Odontobutis obscura (O. obscura) is a crucial commercial species of freshwater fish; however, its molecular biology research is still undeveloped, including its innate immune system, which is pivotal to antiviral response. In this study, we cloned and identified the characterization and kinase function of dark sleeper TANK-binding kinase 1 (TBK1), supplementing the evidence of the conservation of this classical factor in fish. First, the ORF of Odontobutis obscurus (O. obscura) TBK1 (OdTBK1) was cloned from liver tissue by RACE-PCR. Subsequent nucleic acid and amino acid sequence analysis suggested that OdTBK1 is homologous with other fish TBK1, and the N-terminal Serine/Threonine protein kinases catalytic domain (S_TKc) and C-terminal coiled coil domain (CCD) are conserved. Subsequently, the cellular distribution demonstrated that OdTBK1 was located in the cytoplasm region. With regard to the identification of functions, OdTBK1 activated several interferon (IFN) promoters’ activity and induced downstream IFN-stimulated genes (ISGs) expression. In a canonical manner, wild-type OdTBK1 significantly phosphorylated interferon regulatory factor 3 (IRF3) but failed when the N-terminal region was truncated. Furthermore, overexpression of OdTBK1 decreased viral proliferation remarkably. Collectively, these data systematically analyzed the characterization and function of OdTBK1, initiating the study of the innate antiviral response of dark sleeper.